Pengaruh lama maserasi daun ketapang merah (Terminalia Catappa L.) terhadap daya hambat Staphylococcus aureus dan Escherichia coli - Berwi Fazri Pamudi; Munira Munira; Rizky Amalia Saha; Muhammad Nasir (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Bengal Almond leaves (Terminalia catappa L.) contain alkaloids, saponins, tannins, polyphenols, quinones, flavonoids and triterpenoids that can function as antibacterial.Objectives: This research was conducted to determine the effect of maceration time of red ketapang leaves (Terminalia catappa L.) on the growth of Staphylococcus aureus and Escherichia coli. Methods: This study was experimental using a completely randomized design (CRD) consisting of 6 treatments, that P0 (aquades), P1 (red ketapang leaf extract with 1 day maceration time), P2 (2 days maceration) P3 (3 days maceration) , P4 (4 days maceration) and P5 (5 days maceration) with 4 replications.Results: Anova test showed that macerated red ketapang leaf extract significantly affected the growth of Staphylococcus aureus and Escherichia coli (p= 0.000). Duncan's further test showed that the largest inhibition zone diameter in Staphylococcus aureus was formed by P2 (2 days maceration time) which was 18.62 mm and there was no significant difference between treatments. Meanwhile, the largest inhibition zone diameter against Escherichia coli was formed by P1 (1 day maceration time) which was 20.25 mm and there was a significant difference between treatments. Conclusion: Ketapang red leaf extract with different maceration times can inhibit the growth of Staphylococcus aureus and Escherichia coli.